Porous membrane as well as preparation method and application thereof
By setting a sacrificial layer on the upper and lower surfaces of the base film of the lithium-ion battery, the accumulation of molten polymers during laser drilling is avoided, and the mechanical strength and flatness of the porous membrane in the lithium-ion battery is solved, and the energy density and safety performance of the battery are improved.
Patent Information
- Application Number
- CN202411246117.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-13
AI Technical Summary
The liquid organic electrolytes in existing lithium-ion batteries have characteristics such as flammable, easy to leak, and easy to volatilize, resulting in safety hazards. The thermal effect generated during laser drilling makes the surface of the porous membrane uneven, reducing mechanical strength, and affecting the energy density of the battery. and safety performance.
By providing a sacrificial layer on the upper and lower surfaces of the base film to be processed, the molten polymer accumulation during laser drilling is avoided. The porous film formed by laser drilling has a high mechanical strength, and a flat porous film is obtained by removing the sacrificial layer.
It improves the mechanical strength and flatness of the porous membrane, avoids the decrease in battery energy density and safety performance, and is suitable for solid and semi-solid state batteries, enhancing the energy density and rate performance of the battery.
Smart Images

Figure CN119115267A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of materials and relates to a porous membrane and a preparation method and application thereof. Background Art
[0002] Commercial lithium-ion batteries currently mainly use organic liquid electrolytes. However, due to the characteristics of organic solvents being flammable, easy to leak, and easy to volatilize, there are potential risks such as battery overcharging and short circuits, which make liquid organic electrolyte lithium-ion batteries have certain safety hazards in use. All-solid-state lithium batteries are expected to solve safety problems such as electrolyte leakage, combustion, and short circuits caused by lithium dendrites piercing the diaphragm in liquid lithium batteries.
[0003] At present, the mainstream solid electrolyte membrane is usually obtained by punching the film. Conventional laser drilling uses a high-power density laser beam to irradiate the processed material, so that the material is quickly heated to the vaporization temperature and evaporates to form holes. It has a fast punching speed and a wide range of applications. It can punch holes on materials of various materials, and can accurately punch holes on continuously moving films. The aperture, density and processing width of the holes can be controlled and adjusted. However, the thermal effect of the laser is strong. The molten polymer produced during the punching process will accumulate on the surface around the hole, forming a significant crater shape, making the surface of the porous membrane uneven, significantly increasing the thickness of the membrane, and reducing the volume energy density of the battery when used in solid electrolytes and semi-solid electrolytes. In addition, the uneven internal stress distribution on the surface of the porous membrane reduces the mechanical strength of the porous membrane, making it difficult to apply to the coating and assembly process of the battery. Summary of the invention
[0004] The invention provides a method for preparing a porous membrane. The method avoids the accumulation of molten polymer generated during laser drilling on the surface of the porous membrane by setting a sacrificial layer, so that the prepared porous membrane has higher mechanical strength.
[0005] The present invention also provides a porous membrane prepared by the above method, and the porous membrane has high mechanical strength.
[0006] The present invention also provides an electrolyte membrane, including the above-mentioned porous membrane. Since the above-mentioned porous membrane has high mechanical strength, the solid electrolyte membrane is used in the battery to avoid the reduction of the battery energy density and ensure that the battery has high safety performance. In addition, since the porous membrane is obtained by laser drilling, it has a larger average pore size than the traditional diaphragm, and its electrolyte filling amount is more. It is also easier to fill the polar electrolyte material into the pores, thereby reducing the overall impedance, and is more suitable for solid-state batteries and semi-solid batteries.
[0007] The present invention also provides a battery having high energy density, safety performance and rate performance.
[0008] The present invention provides a method for preparing a porous membrane, comprising the following steps:
[0009] 1) Disposing a second base film and a third base film on the upper surface and the lower surface of the first base film respectively to obtain a composite base film;
[0010] 2) performing laser drilling on the composite base film to obtain a composite porous film; the composite porous film comprises a third porous film layer, a first porous film layer and a second porous film layer stacked in sequence;
[0011] 3) removing the third porous membrane layer and the second porous membrane layer in the composite porous membrane to obtain the porous membrane.
[0012] In the preparation method as described above, the thickness of the porous membrane is 5 to 20 μm.
[0013] In the preparation method as described above, the thickness of the second base film and the third base film are respectively 0.2 to 1 times the thickness of the first base film.
[0014] As described above, the materials of the first base film, the second base film and the third base film independently include one or more of polyethylene terephthalate, polyimide, polybutylene terephthalate, polyethylene naphthalate, polyetheretherketone, polyphenylene sulfide and polybenzimidazole.
[0015] The preparation method as described above, wherein the light source for the laser drilling process is selected from an infrared laser light source;
[0016] And / or, the power of a single light source for the laser drilling process is 20W to 200W.
[0017] The preparation method as described above, wherein a release layer is further provided on the surface of the second base film and / or the third base film facing the first base film;
[0018] And / or, the second base film and / or the third base film further comprises 0.5 wt % to 1.5 wt % of an antistatic agent.
[0019] A second aspect of the present invention provides a porous membrane prepared by the preparation method described above.
[0020] A third aspect of the present invention provides an electrolyte membrane comprising the porous membrane as described above.
[0021] The electrolyte membrane as described above, wherein the electrolyte membrane comprises a porous membrane and a solid electrolyte filled in pores of the porous membrane.
[0022] A fourth aspect of the present invention provides a battery comprising the electrolyte membrane as described above.
[0023] The implementation of the present invention has at least the following advantages:
[0024] 1) The method for preparing the porous membrane provided by the present invention can protect the base membrane to be processed by setting a base membrane as a sacrificial layer on the upper and lower surfaces of the base membrane to be processed into a finished porous membrane, thereby avoiding the accumulation of molten polymer on its surface during laser drilling, and the sacrificial layer is easy to remove after the laser drilling is completed, thereby obtaining a porous membrane with higher mechanical strength.
[0025] 2) The electrolyte membrane of the present invention includes a porous membrane prepared by the above method, so the electrolyte membrane can avoid the decrease in battery energy density and safety performance caused by surface unevenness in the battery. In addition, since the above porous membrane is obtained by laser drilling, it has a larger average pore size than traditional diaphragms and is more suitable for application in solid-state batteries and semi-solid-state batteries.
[0026] 3) Since the battery of the present invention includes the above-mentioned electrolyte membrane, the battery has high energy density, safety performance and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is a SEM image of the porous membrane of Example 1 of the present invention;
[0028] Figure 2 This is a SEM image of the porous membrane of Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] A first aspect of the present invention provides a method for preparing a porous membrane, comprising the following steps:
[0031] 1) Disposing a second base film and a third base film on the upper surface and the lower surface of the first base film respectively to obtain a composite base film;
[0032] 2) performing laser drilling on the composite base film to obtain a composite porous film; the composite porous film comprises a third porous film layer, a first porous film layer and a second porous film layer stacked in sequence;
[0033] 3) removing the third porous membrane layer and the second porous membrane layer in the composite porous membrane to obtain a porous membrane.
[0034] The preparation method provided by the present invention first sets the second base film and the third base film as sacrificial layers on the upper and lower surfaces of the first base film respectively, and then performs laser drilling treatment on the formed composite base film with a three-layer structure, so that porous structures are formed on the three-layer film to obtain a composite porous membrane. The thermal effect generated during the laser drilling process makes the molten material of the membrane material mainly concentrated on the surfaces of the upper and lower sacrificial layers, while the surface of the holes formed in the middle layer of the membrane has no melt deposition and has a higher flatness. Finally, the third porous membrane layer and the second porous membrane layer as sacrificial layers in the composite porous membrane are removed to obtain the porous membrane of the present invention.
[0035] The porous membrane obtained by the preparation method of the present invention has no obvious melt deposition on the pore surface, and can avoid the problem of decreased battery energy density caused by a significant increase in the thickness of the diaphragm when applied to the diaphragm. The internal stress caused by the local thermal effect generated during the laser drilling process is mainly concentrated on the sacrificial layer, and the porous membrane finally obtained has less uneven internal stress distribution, so the porous membrane maintains a higher mechanical strength.
[0036] The present invention does not limit the arrangement of the second base film and the third base film on the upper and lower surfaces of the first base film, as long as the second base film is completely attached to and covers the upper surface of the first base film, the third base film is completely attached to and covers the lower surface of the first base film, and the relative positions of the three do not change during the punching process.
[0037] In a preferred embodiment, the thickness of the porous membrane is 5-20 μm. For example, the thickness of the porous membrane can be 5 μm, 8 μm, 12 μm, 15 μm, 20 μm, or a range consisting of any two values therein.
[0038] When the thickness is thin, the channel for ion migration is shorter, which can avoid polarization of the battery, but the safety is poor. When the thickness is thick, it can better ensure the isolation of the positive and negative electrodes to avoid short circuit of the battery when impacted by foreign objects. The above thickness range is conducive to making the battery have both good ion transmission performance and safety performance.
[0039] In a preferred embodiment, the thickness of the second base film and the thickness of the third base film are 0.2 to 1 times the thickness of the first base film, respectively. Within the above thickness relationship range, the second base film and the third base film can provide sufficient protection for the first base film, and the waste of materials caused by the excessive thickness of the sacrificial layer can be avoided. Exemplarily, the thickness of the second base film and the thickness of the third base film can be 0.2 times, 0.4 times, 0.6 times, 0.8 times, 1 times, or any range consisting of the above values, respectively, of the thickness of the first base film.
[0040] The present invention does not specifically limit the materials of the first base film, the second base film and the third base film, and the materials of the three can be the same or different. Further, the materials of the first base film, the second base film and the third base film independently include one or more of polyethylene terephthalate (PET), polyimide (PI), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), polyetheretherketone (PEEK), polyphenylene sulfide (PPS), and polybenzimidazole (PBI). The above polymers have good heat resistance, which can make the porous membrane have a higher film breaking temperature and is safer to use under high temperature conditions.
[0041] The present invention does not specifically limit the device for laser drilling processing, and the laser drilling processing can be performed by selecting a conventional laser drilling device in the art. For example, an array laser drilling device can be used for drilling.
[0042] In a specific embodiment, the light source for laser drilling is selected from an infrared laser light source, preferably a gas laser capable of emitting infrared light. The infrared laser light source has a strong thermal effect and can quickly form holes on the base film to improve the preparation efficiency of the porous film.
[0043] In the present invention, different types of infrared laser light sources can be selected according to the required pore size of the porous membrane. For example, for a porous membrane with a pore size of more than 10 μm, a CO2 laser is preferred; for a porous membrane with a pore size of about 5 μm, a HBr laser with a shorter wavelength is preferred.
[0044] In a preferred embodiment, the power of a single light source for laser drilling is 20W to 200W. The power of a single light source refers to the power of a single excited optical element during dot matrix drilling or dense drilling. If the power is too high, it is easy for the surface of the base film in the middle to accumulate melt during the processing; if the power is too low, it is difficult to achieve the required processing efficiency. Exemplarily, the power of a single light source for laser drilling can be 20W, 40W, 60W, 80W, 100W, 120W, 140W, 160W, 180W, 200W, or a range consisting of any two of these values.
[0045] In an optional embodiment, a release layer is further provided on the surface of the second base film and / or the third base film facing the first base film.
[0046] The provision of the release layer can reduce the adhesion between the second base film and / or the third base film and the first base film, making them easier to remove and avoiding damage to the porous film during the removal process.
[0047] Further, the release layer includes an organosilicon release agent and / or a fluorine release agent. The present invention does not specifically limit the types of the organosilicon release agent and the fluorine release agent, which can be selected from the organosilicon release agent and the fluorine release agent conventionally used in the art. For example, the organosilicon release agent can be selected from one or more of Wacker SILRES, Dow Corning SYL-OFF7920, and Shin-Etsu KS774, and the fluorine release agent can be selected from one or more of Dow Corning's SYL-OFF Q2-7786 and SYL-OFF Q2-7555, and Shin-Etsu's X-70-410, X-70-411, X-70-201S, and X-70-1601.
[0048] The second base film and the third base film with release layers can be directly used by selecting commercially available heat-resistant release films, or can be prepared by themselves.
[0049] In a specific embodiment, taking the release layer including Dow Corning's SYL-OFF Q2-7785 fluorochemical release agent as an example, the preparation method of the base film having a release layer includes the following steps: dissolving Corning SYL-OFF Q2-7785 in n-hexane or n-heptane at a solid content of 25%, adding a cross-linking agent SYL-OFF Q2-7560 based on a mass fraction of the release agent of 3.2% to obtain a release layer slurry, and then coating the release layer slurry on the surface of the base film, and curing at 100°C for 7 days to obtain a base film having a release layer.
[0050] In order to improve the adhesion between the second base film and / or the third base film and the first base film, an antistatic agent may be added to the second base film and / or the third base film. In a preferred embodiment, the second base film and / or the third base film also include 0.5wt% to 1.5wt% of an antistatic agent. Exemplarily, the mass content of the antistatic agent may be 0.5wt%, 0.8wt%, 1.0wt%, 1.2wt%, 1.5wt% and a range consisting of any two of these values.
[0051] The type of the antistatic agent of the present invention is not specifically limited, and it can be selected from conventional cationic antistatic agents, anionic antistatic agents or nonionic antistatic agents. Exemplary, the antistatic agent can be selected from cationic quaternary ammonium salt antistatic agents or ethoxylated alkylamine antistatic agents. The base film including the antistatic agent can be obtained by coating the antistatic agent on the surface of the base film after being formulated into a solution, or by doping the antistatic agent into the raw material of the base film and preparing it by mixing and extruding.
[0052] The second aspect of the present invention provides a porous membrane, which is prepared by the preparation method described above. Since sacrificial layers are arranged on the upper and lower surfaces of the base membrane to be processed, the molten polymer generated during the laser drilling process accumulates on the surface of the sacrificial layer, and the surface of the base membrane to be processed does not accumulate molten polymer, so the surface of the porous membrane of the present invention has a higher flatness, less uneven internal stress distribution around the pores, and higher mechanical strength.
[0053] The third aspect of the present invention provides an electrolyte membrane, including the porous membrane as described above. Since the porous membrane has a high surface flatness, the electrolyte membrane also has a high surface flatness, and will not cause excessive increase in battery thickness when used in batteries, thereby avoiding negative impacts on battery volume energy density. In addition, since the porous membrane formed by laser drilling has a larger average pore size than the traditional nanoscale pore diaphragm, it has a larger electrolyte filling amount, and it is also easier to fill polar electrolyte materials into the pores, thereby reducing the overall impedance, so it is more suitable for application scenarios of solid-state batteries or semi-solid-state batteries.
[0054] In a preferred embodiment, the electrolyte membrane of the present invention comprises a porous membrane and a solid electrolyte filled in the pores of the porous membrane.
[0055] The average pore size of the porous membrane formed by laser drilling is large, which can easily cause battery short circuit. Filling the porous membrane with solid electrolyte can reduce the directness of the pores, reduce the probability of battery short circuit, and improve the insulation strength of the solid electrolyte membrane. Compared with the traditional diaphragm that only coats the solid electrolyte layer on the surface of the base membrane, filling the solid electrolyte in the pores of the porous membrane can make the battery have a lower Gurley permeability value and better ion conduction characteristics, which is beneficial to the transmission of lithium ions and can improve the battery's rate performance.
[0056] The present invention does not specifically limit the type of the above-mentioned solid electrolyte, which can be selected from solid electrolytes conventionally used in the art, including but not limited to one or more of oxide solid electrolytes, polymer solid electrolytes, sulfide solid electrolytes, and gel electrolytes. Among them, the oxide solid electrolyte is preferably aluminum titanium phosphate (LATP) or lithium lanthanum zirconium oxide (LLZO), the polymer solid electrolyte is preferably copolymer-modified polyethylene oxide (PEO), and the sulfide solid electrolyte is preferably Li6PS5Cl.
[0057] In a specific embodiment, the electrolyte membrane comprising a porous membrane and a solid electrolyte filled in the pores of the porous membrane can be prepared by the following method:
[0058] The solid electrolyte is made into slurry and then coated on the porous membrane, and then dried and solidified to obtain the electrolyte membrane.
[0059] The coating method can be selected from one or more of screen roller coating, wire rod coating, dip coating and extrusion coating; the drying temperature is preferably 60-80°C.
[0060] The fourth aspect of the present invention provides a battery, comprising the above-mentioned separator. Since the above-mentioned separator has good surface flatness, high mechanical strength, low Gurley value and better ion conductivity, the battery has a low internal impedance of the battery while maintaining a high energy density, so that the battery has a high rate performance.
[0061] The battery of the present invention can be a liquid battery, a solid-state battery and a semi-solid-state battery, and more preferably a solid-state battery and a semi-solid-state battery. In addition to the above-mentioned electrolyte membrane, the battery of the present invention also includes a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet and the negative electrode sheet can refer to the positive electrode sheet and the negative electrode sheet conventionally used in lithium-ion batteries, and will not be repeated here.
[0062] The porous membrane provided by the present invention and its preparation method and application will be further described in detail below through specific examples. Obviously, the following examples are only some embodiments of the present invention, not all embodiments. Based on the technical solutions and given embodiments provided by the present application, all other embodiments obtained by those skilled in the art without creative work are within the protection scope of the present invention.
[0063] Example 1
[0064] This embodiment provides a porous membrane, a solid electrolyte membrane and a lithium ion battery, and the specific preparation method is as follows:
[0065] 1. Preparation of porous membrane
[0066] 1) stacking and unwinding a second base film (PET material) with a thickness of 10 μm, a first base film (PET material) with a thickness of 5 μm, and a third base film (PET material) with a thickness of 5 μm in sequence, and performing thermal lamination and heat setting at 120° C. to obtain a composite base film;
[0067] 2) performing laser drilling on the composite base film using an array laser drilling device to obtain a composite porous film having a third porous film layer, a first porous film layer, and a second porous film layer stacked in sequence;
[0068] The light source in the laser drilling process is selected from CO2 laser, the laser wavelength is selected from 10.6 μm, and the power of a single light source is 20 W;
[0069] 3) Rolling up in layers, removing the third porous membrane layer and the second porous membrane layer in the composite porous membrane, and obtaining a porous membrane.
[0070] 2. Preparation of solid electrolyte membrane
[0071] 1) adding 50 parts by weight of solid electrolyte powder LATP, 0.5 parts by weight of thickener CMC, 0.25 parts by weight of dispersant BYK-156, 5 parts by weight of adhesive GR401, 0.1 parts by weight of wetting agent BYK-348, and 50 parts by weight of deionized water into a double planetary slurry kettle, stirring at 2000 rpm / min for 120 min to obtain a coating slurry;
[0072] 2) The above-mentioned coating slurry is coated on the porous membrane prepared in step 1 by a dip coating process, and dried at a temperature of 60° C. to 80° C. to obtain a solid electrolyte membrane.
[0073] 3. Preparation and assembly of batteries
[0074] 1) The positive electrode active material NCM811, the conductive agent SP, the conductive agent KS-6, and the binder PVDF are mixed in a solvent NMP in a mass ratio of 90:2:1:3 to form a positive electrode slurry, which is then coated on a 10 μm aluminum foil current collector; then dried in an oven at 95°C, and rolled on a roller press for use.
[0075] 2) The active material artificial graphite, the conductive agent acetylene black and the binder CMC / SBR are evenly dispersed in water at a mass ratio of 90:5:5 to form a negative electrode slurry, which is coated on a copper foil current collector with a thickness of 10 μm, dried in an oven at 85°C, and rolled on a roller press for use.
[0076] 3) In a drying room with a dew point of <-40°C, the solid electrolyte composite membrane of the present invention is placed between the positive electrode sheet and the negative electrode sheet for stacking and packaging, and the solid electrolyte composite membrane is heated at 2.5 g / m 2 The electrolyte (Xinzhoubang, LBC3008A) was injected in a proportion of to obtain a battery.
[0077] The porous membrane prepared in Example 1 was subjected to SEM testing. Figure 1 is the SEM image of the porous membrane, such as Figure 1 As shown, after adding the sacrificial layer, the surface of the porous membrane has no obvious crater shape and has a high flatness.
[0078] Embodiments 2 to 6
[0079] Examples 2 to 6 provide a porous membrane, a solid electrolyte membrane, and a lithium ion battery, respectively, wherein the materials and thicknesses of the first base membrane, the second base membrane, and the third base membrane used in the preparation process of the porous membrane are different from those in Example 1, and the preparation conditions of the solid electrolyte membrane and the lithium ion battery are the same as those in Example 1. The differences between the preparation conditions of the porous membrane and Example 1 are listed in Table 1, and for ease of comparison, the conditions corresponding to Example 1 are also listed in Table 1.
[0080] Table 1
[0081]
[0082] Example 7
[0083] This embodiment provides a porous membrane, a solid electrolyte membrane and a lithium ion battery, wherein the preparation method of the porous membrane is different from that of embodiment 1 only in that the power of the single light source in the laser drilling is replaced with 60 W. The preparation conditions of the solid electrolyte membrane and the lithium ion battery are the same as those of embodiment 1.
[0084] Example 8
[0085] This embodiment provides a porous membrane, a solid electrolyte membrane and a lithium ion battery, wherein the preparation method of the porous membrane is different from that of embodiment 1 only in that the light source is replaced from a CO2 laser to a semiconductor pump laser, the wavelength of the light source is 808nm, and the drilling power is 40W. The preparation conditions of the solid electrolyte membrane and the lithium ion battery are the same as those of embodiment 1.
[0086] Example 9
[0087] This embodiment provides a porous membrane, a solid electrolyte membrane and a lithium ion battery, wherein the preparation method of the porous membrane is different from that of Example 1 only in that the second base membrane and the third base membrane each contain 0.5 wt% of a cationic quaternary ammonium salt antistatic agent. The preparation conditions of the solid electrolyte membrane and the lithium ion battery are the same as those of Example 1.
[0088] Example 10
[0089] The present embodiment provides a porous membrane, a solid electrolyte membrane and a lithium ion battery, wherein the preparation method of the porous membrane is different from that of Example 1 only in that: step 1) is replaced by: dissolving Dow Corning SYL-OFF Q2-7785 in n-hexane at a solid content of 25%, adding a cross-linking agent SYL-OFF Q2-7560 based on a mass fraction of a release agent of 3.2%, to obtain a release layer slurry, and then coating the release layer slurry on one side of a 5 μm PET film surface, and curing at 100° C. for 7 days to obtain a second base film and a third base film having a 1 μm release layer, and stacking and unwinding the second base film, the first base film and the third base film in sequence (so that the second base film and the third base film provided with the release layer are both facing the first base film), and thermally compounding and heat-setting are performed at 120° C. to obtain a composite base film.
[0090] Comparative Example 1
[0091] This comparative example provides a porous membrane, a separator including the porous membrane, and a lithium ion battery, and the specific preparation method is as follows:
[0092] Preparation of porous membrane: A PET membrane with a thickness of 10 μm was laser punched using an array laser punching device to obtain a porous membrane; wherein the light source in the laser punching process is selected from a CO2 laser, the laser wavelength is 10.6 μm, and the single light source power is 20 W.
[0093] The preparation conditions of the solid electrolyte membrane and the battery are the same as those in Example 1 and will not be repeated here.
[0094] The porous membrane prepared in this comparative example was subjected to SEM testing. Figure 2 The SEM image of the porous membrane of Comparative Example 1 is shown in Figure 2 As shown, the porous membrane surface obtained without setting a sacrificial layer on the membrane surface to be processed has obvious melt deposition around each pore, presenting an obvious crater shape, and the surface flatness of the porous membrane obtained is low.
[0095] Test Case
[0096] 1. The following properties of the porous membranes of the above embodiments and comparative examples were tested:
[0097] 1. Average thermal shrinkage at 200℃
[0098] Test method: Referring to GB / T36363-2018, the porous membrane was placed in a 200°C environment, treated for 1 hour, and the thermal shrinkage in MD and TD directions was calculated. The average value of the thermal shrinkage in MD and TD directions was taken as the average thermal shrinkage at 200°C.
[0099] 2. MD tensile strength
[0100] Test method: refer to GB / T36363-2018.
[0101] 3. Puncture strength
[0102] Test method: refer to GB / T36363-2018.
[0103] 4. Porosity
[0104] Test method: refer to GB / T36363-2018.
[0105] 5. Membrane breaking temperature
[0106] Test method: The porous membrane is placed in a tensioned state (simulating the state inside a battery), and the temperature is gradually raised to the point where the membrane breaks. The temperature at which the membrane breaks is the membrane breaking temperature of the porous membrane.
[0107] 6. Surface roughness S a
[0108] Test method: Use Olympus LEXT OLS5100 laser confocal microscope to test. Fix the porous membrane on the sample stage, adjust the objective lens magnification to 10X and start 3D acquisition scanning. Then click on the Correct Tilt tab in the analysis software, and select the Height / Mixed mode to calculate the surface roughness S under no filtering conditions. a Value. a The value is calculated as follows:
[0109]
[0110] 2. The following performance tests were performed on the solid electrolyte membranes of the above embodiments and comparative examples:
[0111] 1. Insulation strength
[0112] Test method: Place the solid electrolyte membrane between two electrodes, apply voltage between the electrodes, increase the voltage until the solid electrolyte membrane is broken down, and take the voltage value when the solid electrolyte membrane is broken down, which is the insulation strength.
[0113] 3. The batteries prepared in the above examples and comparative examples were tested for the following properties:
[0114] 1. Energy density
[0115] Test method: Test the soft-pack battery in the voltage range of 3.0V to 4.5V. The discharge platform voltage can be determined by cyclic voltammetry at a rate of 0.5C. Then, discharge at a constant current of 1C in a fully charged state to measure the discharge capacity. The volume energy density is calculated by the following formula:
[0116]
[0117] The test results of all the above performances are shown in Table 2.
[0118] Table 2
[0119]
[0120] The following conclusions can be drawn from Table 2:
[0121] 1) By comparing Examples 1 to 4, 6, 9, and 10 with Comparative Example 1, it can be seen that the porous membrane formed by laser punching after compounding a sacrificial layer on the upper and lower surfaces of the base membrane to be processed (the first base membrane) has less molten polymer on the surface, smaller surface roughness of the porous membrane, higher porosity, better tensile strength and puncture strength, and the solid electrolyte membrane prepared using this type of porous membrane has better insulation strength and a higher volume energy density of the battery prepared.
[0122] 2) By comparing Examples 1 to 4 and 6, it can be seen that the greater the thickness of the composite sacrificial layer on the upper and lower surfaces of the base film to be processed, the smaller the surface roughness of the porous film formed by the final processing, the higher the film breaking temperature of the porous film, the better the tensile strength and puncture strength of the porous film, and the higher the insulation strength of the solid electrolyte membrane prepared by the film. In addition, when the thickness of the upper and lower sacrificial layers is 0.2 to 1 times the thickness of the base film to be processed (Examples 1 to 4), the base film to be processed to form a porous film can be well protected, and the safety performance and mechanical strength of the porous film obtained are relatively excellent. When the thickness of the upper and lower sacrificial layers is 0.1 times the thickness of the base film to be processed (Example 6), the surface roughness of the porous film is significantly improved, the thermal shrinkage rate is significantly improved, the tensile strength is significantly reduced, and the volume energy density of the battery is also significantly reduced when used in the battery.
[0123] 3) By comparing Example 1 and Example 5, it can be seen that compared with the base film made of PET material, the surface roughness of the porous membrane formed by laser punching the base film of PI material is smaller, the porosity is higher, and there is no thermal yield phenomenon when heated at 200°C for 1h. The porous membrane has a high membrane rupture temperature and higher thermal safety performance. It has higher insulation strength and volume energy density when applied to solid electrolyte membranes and batteries, but its tensile strength and puncture strength are relatively low.
[0124] 4) By comparing Examples 1, 9, and 10, it can be seen that after adding an antistatic agent or a release layer to the sacrificial layer, the sacrificial layer can be removed after the processing is completed, and the performance of the formed porous membrane is basically not affected.
[0125] 5) By comparing Examples 1 and 7, it can be seen that when laser drilling is performed at a single light source power of 20 W and 60 W, the surface roughness, porosity, thermal shrinkage rate, film rupture temperature, tensile strength, puncture strength, etc. of the porous membrane formed are basically the same, and there is no difference in insulation strength and volume energy density when applied to solid electrolyte membranes and batteries.
[0126] 6) By comparing Example 1 with Example 8, it can be seen that the surface roughness of the porous membrane formed by drilling with a semiconductor pumped laser light source is smaller, the average thermal shrinkage rate is smaller, and the tensile strength and energy density of the battery are also better.
[0127] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may still be modified, or some or all of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a porous membrane, characterized in that: The following steps are involved: 1) Arranging a second base film and a third base film on the upper surface and the lower surface of the first base film respectively to obtain a composite base film, wherein the second base film and / or the third base film is a base film or a film layer having a pore size smaller than a target processing pore size; 2) performing laser drilling on the composite base film to obtain a composite porous film; the composite porous film comprises a third porous film layer, a first porous film layer and a second porous film layer which are stacked in sequence; 3) removing the third porous membrane layer and the second porous membrane layer in the composite porous membrane to obtain the porous membrane.
2. The preparation method according to claim 1, characterized in that: The thickness of the porous membrane is 5 to 20 μm.
3. The preparation method according to claim 1 or 2, characterized in that: The thickness of the second base film and the third base film are respectively 0.2 to 1 times the thickness of the first base film.
4. The preparation method according to claim 1, characterized in that: The materials of the first base film, the second base film and the third base film independently include one or more of polyethylene terephthalate, polyimide, polybutylene terephthalate, polyethylene naphthalate, polyetheretherketone, polyphenylene sulfide and polybenzimidazole.
5. The preparation method according to claim 1, characterized in that: The light source for the laser drilling process is selected from an infrared laser light source; And / or, the power of a single light source for the laser drilling process is 20W to 200W.
6. The preparation method according to claim 1 or 4, characterized in that: A release layer is also provided on the surface of the second base film and / or the third base film facing the first base film; And / or, the second base film and / or the third base film comprises 0.5 wt % to 1.5 wt % of an antistatic agent.
7. A porous membrane, characterized in that The preparation method is described in any one of claims 1 to 6.
8. An electrolyte membrane, characterized in that: Comprising the porous membrane according to claim 7.
9. The electrolyte membrane according to claim 8, characterized in that The electrolyte membrane includes a porous membrane and a solid electrolyte filled in pores of the porous membrane.
10. A battery, characterized in that: Comprising the electrolyte membrane according to claim 9.
